Approximate solution of the two-dimensional Rayleigh-Stokes problem for a heated generalized second grade fluid with fractional derivatives - Rashidinia, Jalil; Parsa, Ali; Salehi, Raheleh (Sulaimani Journal for Pure and Applied Sciences, 2016)
In this paper, a scheme based on Sinc and radial basis functions (RBF) is developed to approximate the solution of two-dimensional Rayleigh-Stokes problem for a heated generalized second-grade fluid with fractional derivatives‎. We use RBF and Sinc functions as basis functions to approximate spatial and time coordinates of the unknown function‎, respectively‎. ‎The error analysis is studied and discussed‎. An illustrative example verifies the effectiveness of our method and shows that one can obtain accurate results with only a small number of basis functions‎.
Keywords: Rayleigh Stokes problem; Fractional calculus; Sinc method; Sinc quadrature; RBFs